Earth observation data to strengthen flood resilience: a recent experience from the Irrawaddy River - Ghosh, Surajit; Mukherjee, J. (Springer, 2023)
The improvement of Earth Observation (EO) sensors and modern computational efficiency in the form of cloud analytics platform has made monitoring and interpretation of floods much more efficient. In this study, we present the recently occurred floods in the north-central section of the Irrawaddy River, inundating the adjoining farmlands on the active floodplains along a stretch of 228 km. The amount of rainfall was observed to have gradually risen from early June 2022 captured through GPM data. Similarly, the water levels in the study stretch were observed to have increased from 98.08 m to 104.08 m (from Sentinel-3 altimetry) due to torrential rains on the northern hilly tracts of Myanmar. High-resolution Sentinel-1 SAR datasets have been used to estimate flood progression in the GEE platform. The total inundated area had risen from 196 to 989 sq. km. throughout June till the first week of July. Thus, EO data associated with accessible computing on cloud platforms help monitor flood progression, warn the community well in advance and support the development of crop insurance strategies, anticipatory actions and many more to strengthen evidence-based flood policy.